An Analysis of Constitutional Amendments on Fundamental Right to Property: Examining the Evolution of Property Rights in the Indian Constitution (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Second Amendment's protection of the right to private property was the second mostcontentious provision fought over during the Constitution's creation, and it was the first fundamental rightto be ultimately negated in 1978, giving it a unique refinement. The Indian State has made consistentefforts to reshape property relations in the public arena to achieve its goals of monetary improvement andsocial redistribution, and this can be seen in the development of the right to property in the Constitutionfrom the drafting of the first established property proviso through legal understanding, enactment, andprotected change. As a legitimate form of social organization, property has different forms under differentlegal systems. The legality of private property ownership is a point of contention between those whosupport the right to own such property and those who oppose it. Land acquisition legislation in India hasa long and tumultuous history, with two clear lines of development one beginning with the Constitutionof India, 1950, which guaranteed the fundamental right to property, and the other beginning with theestablishment of the Land Acquisition Act, 1894. Not only should both be studied simultaneously, but inrecent years they have both moved freely and independently of one another.